Combating money laundering by preventing doubtful operations on withdrawal of cash - I. A. Krestovskii (Путеводитель предпринимателя)
In the Annex 1 Provisions of the Bank of Russia dated 02.03.2012 № 375-P presents a number of dubious operations. However, the greatest interest is section 14, «evidence on the possible implementation of the legalization (laundering) of the incomes received by a criminal way, at carrying out operations with monetary funds in the form ofcash and transfers of funds». The ultimate goal of money laundering is the withdrawal of capital in the form of cash or transfer offunds to Tax haven. It is about illegal receipt of cash will be discussed in this article or, as it is now called Anti-Money Laundering experts, about «cashing in».